2021
DOI: 10.1002/jhbp.994
|View full text |Cite
|
Sign up to set email alerts
|

Detection of actionable mutations in archived cytological bile specimens

Abstract: Background/Purpose: There are limitations in obtaining sufficient pancreaticobiliary tumor tissue for genomic profiling of tumors. Herein, we investigated whether archived cytological specimen (ACS) is suitable for genomic profiling to identify oncogenic and drug-matched mutations. Methods: We constructed a pancreaticobiliary cancer panel for targeted sequencing covering 60 significantly mutated genes (280 220 bp). Eighty DNA samples ( 19formalin-fixed paraffin-embedded [FFPE] tissues and 61 ACS) from 44 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Ascites fluid was collected at the same time as the surgically resected specimens. The preparation of DNA from cytology specimens was done as previously described 9 . Briefly, a glass slide was soaked in xylene for 1 to 7 days, then the coverglass was removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascites fluid was collected at the same time as the surgically resected specimens. The preparation of DNA from cytology specimens was done as previously described 9 . Briefly, a glass slide was soaked in xylene for 1 to 7 days, then the coverglass was removed.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of DNA from cytology specimens was done as previously described. 9 Briefly, a glass slide was soaked in xylene for 1 to 7 days, then the coverglass was removed. The tumor-rich clusters were peeled off from the glass slides with a razor blade and processed (Fig.…”
Section: Preparation Of Formalin-fixed Paraffin-embedded Tissues and ...mentioning
confidence: 99%
“…FFPE tumor tissue was microdissected by LCM using Arcturus CapSure Macro LCM Caps (Thermo Fisher Scientific) on an Arcturus XT system (Thermo Fisher Scientific). FFPE DNA was extracted using the GeneRead DNA FFPE Kit (Qiagen) according to the manufacturer's instructions 31 …”
Section: Methodsmentioning
confidence: 99%
“…FFPE DNA was extracted using the GeneRead DNA FFPE Kit (Qiagen) according to the manufacturer's instructions. 31…”
Section: Extraction Of Ffpe Dnamentioning
confidence: 99%
“…Han et al 49 reported bile-derived miR-30d-5p and miR-92a-3p as biomarkers for CCA; however, 81.1% SN and 60.5% SP were insufficient due to the diversity of mutations in biliary genes. A study by Ohyama et al 50 suggested that genomic profiling of archived bile cytological specimens with NGS-based targeted sequencing could discriminate between malignant and benign disorders with 93% accuracy, 91% SN, and 100% SP, including six cases (6/44 = 13.6%) with stage I BTC using a 60-gene panel. All six patients had ≥1 gene mutations (KRAS 1/6; TP53, 3/6; ERBB2, 2/6; ERBB3, 2/6; and SMAD4, 3/6 cases).…”
Section: Genomicsmentioning
confidence: 99%